Development of separate-type Pt-free photofuel cells based on visible-light responsive TiO2 photoanode - Iyatani, Kazushi; Horiuchi, Yu; Moriyasu, Madoka; Fukumoto, Shohei; Cho, So-Hye; Takeuchi, Masato; Matsuoka, Masaya; Anpo, Masakazu (ROYAL SOC CHEMISTRY, 2012)
Development of efficient Pt-free photofuel cells employing two different electrolytes containing various biomass derivatives and an I3(-)/I- redox solution for the anode and cathode sides, respectively, is described. These new, separate-type photofuel cells exhibit good photoelectrochemical performance under simulated solar-light irradiation.
Keywords: MICROBIAL FUEL-CELLS; PHOTOELECTROCHEMICAL REACTION; FILM PHOTOANODE; THIN-FILMS; WATER; PHOTOCATALYSIS; HYDROGEN; PERFORMANCE; ELECTRICITY; GENERATION